Puccini's Tosca - Illica, Luigi, 1857-1919 (Opera classics library., 2002)
Puccini's Tosca is a high-voltage, powerful and sensational opera thriller that is crammed with actoin, intense, and sometimes ferocious, supercharged dramatic confrontations: a true music drama.